The Influence Of Spirituality And Resilience On Achievement Motivation Among Yemeni Refugee Students In Saudi Arabia - Garoon, Manal Ali Ahmed (2022)
Yemeni refugees have been exposed to various types of misfortune and risk, the most prominent of which has been the war crisis that has forced them to flee from Yemen to Saudi Arabia due to critical conflict since 2015. As a result, several psychological problems caused by war have emerged. From the perspective of educational psychology issues, achievement motivation is considered a critical concern in this area. Given the near absence of studies that have examined both the spirituality and resilience of refugees and their influence on achievement motivation, this study aimed to identify the influence of spirituality and resilience on achievement motivation among Yemeni refugee students who have been displaced to Saudi Arabia. This study proposed a new conceptual framework based on spirituality from the Islamic perspective, resilience theory by Masten (2014), and achievement motivation theory by Atkinson (1964). This research study applied a sequential explanatory mixed-method approach. A snowball sample of 209 participants were recruited and supplemented the quantitative phase of the study. Thereafter, a purposeful sample of 10 participants were recruited so as to complete the qualitative phase of the study.